THE EFFORT TO INCREASE STUDENT’S LEARNING OUTCOMES USING COOPERATIVE LEARNING EXAMPLE NON EXAMPLE - Mardanis, Mardanis; Sudargono, Agus; Rahman, MS Khabibur (Journal of Geography Science and Education, 2019)
The purpose of this study was to determine the effect of the example non example method about the dynamics of the hydrosphere and its impact on the life of social science learning. The sample of this study is class X IPS 4 in STATE 3 HIGH SCHOOL, Sukoharjo. This is Classroom Action Research study that used Example Non Example method using images. The result showed that the learning outcomes of students was increased from 83,11% to 86,33% at the first Cycle and continued to increase to 91,67% at the second cycle.  Keywords: Learning Outcomes, Example Non Example